Forced Back into the Closet: A (Queer) Principal's Attempt to Maintain Queer Erasure. (December 2020) - Duarte, Bryan J.
This case adds to a lack of research that considers the intersection of queer identities and educational leadership. The case narrative demonstrates the complex nuances of two negotiated professional queer identities. In addition, the case considers the consequences of queer erasure on the existing heteronormative culture of schooling. The teaching notes review the literature on queer school professionals and provide a background for understanding the geographical and historical considerations of LGBTQ+ (lesbian, gay, bisexual, transgender, transsexual, queer) identities in schools. The author concludes with a plea to both heterosexual and queer school leaders and those who prepare them to reflect on their position and responsibilities within a heteronormative and heterosexist field. The activities and discussion questions are designed with these aims in mind.